Improving growth, physiology and yield of rice plants and nutrients under different water regimes using proline - Mohd Khairi Che Lah
Water stress due to climate change affects plant growth, physiology and yield production. It is an important concern, nowaday, to increase water productivity and sustain rice production under water stre s condition. Water stress is detrimental to agricultural production and plant ecosystem . Irrigated rice consumes a larger amount of fresh water which to be reduced using low water input rice production and saved water to be diverted to the areas where competition is high. In this study, the function of proline was justified to reduce the detrimental effects of water stress on growth, physiology, yield parameters and nutrients of rice plant to maintain sustainable rice production under water stress condition. The first experiment was conducted to observe the effects of different water levels on rice production. The second experiment (greenhouse) and third experiment (field) were done to find out the effects of proline and different water levels on growth, physiological parameters, and rice production. Both experiments were laid out in a completely randomized design with five replicates. In the first experiment four different water treatments, WI (field capacity), W2 (saturated condition), W3 (1 ern flooding) and W4 (5 em flooding; control treatment) were used. In the econd and third experiments, proline concentrations (0, 50 ~ttr 1'0 (i'pM as a foliar were used with four water levels (as per experiment 1 with five replication. he fourth experiment was conducted to determin nutrients content under proline and water content. In the first experiment, chlorophyll ( hl), Chi fluore cence param photosynthesi rate (Pn rate), phot synthetically active radiation (PAR), transpiration rate, stomat l conductance (SC) and relative water content (R W ) decreased in I treatments. Soil pH, electrical conductivity (EC), and redox potential (Eh value) howed the lowe t value in WI and W2 treatments. However, Eh value of W4 was significantly lower than other treatment. WI and W2 treatments significantly affected yields and yield parameters of rice plants compared t W4 treatment. For experiment 2, proline improves germination and root length of the seedling. Application of proline significantly increased plant height and R we of rice plant under WI and W2 treatment. Chi content, SC, Fo, Frn and Fv/Fm ratio significantly increased in proline¬treated plant than proline-untreated plants under WI and W2 treatments. Treatments of WI and W2 significantly reduced C02-in leaf, PAR, Pn rates, and transpiration rate which were increased in the proline-treated plants. In field experiment 3, proline showed a similar effect on growth, physiology and yield parameters of rice plants under water stress condition. Results in experiment 3 were consistent with experiment 2. Proline also increased photochemical quenching (ql), non-photochemical quenching (qn and NPQ) activities in leaves in rice plants which might increase photosynthesis rate. In experiment 4, phytoavailability of nutrients were analyzed under two different wat r depths that are 1 and 5 ern flooding in the presence or absence of 50 mM of proline. Proline application did not affect phytoavailability of Nand P in soil solution. Proline treatment affected K concentration but the level was not too high. Proline improves Ca, Mg and other micronutrients' concentration in soil with I cm than that of 5 cm flooding condition. However, there is no significant effect of proline on Eh value, soil pH and soil EC was observed. These results suggest that under water stress (WI and W2 treatments) condition, proline reduced the detrimental effects of water stress growth, physiology and yield of rice plants. Therefore the physiological changes, nutrients' phytoavailability and rice production under stres conditions (WI and W2) were consistent with control treatment and low water input rice producti n can help to save the fresh water and sustain rice production. Farmers could apply irrigation water as alternative wetting and drying condition that is field capacity to the I ern tlooding, to ustain rice production and proline could be implement d where climate change effect persist in declining water status in oil.